The Influence of Investment on the Probability of Tencent Ltd Period 2008 – 2022 - Fauriza Prameswari Gunadi; Risma Nurmilah; Irfan Sophan Himawan (International Journal of Business and Applied Economics, 2023)
This research examines the influence of investment on profitability at Tencent Ltd. The data used is secondary data, which is the financial statements of Tencent Ltd. for the period 2008–2022. The method used is quantitative with multiple linear regression analysis, coefficient of determination, t-test, and F-test by processing data using Eviews software 10. The results show that Investment Cash Flow and Dividend income, which are Investment variables, have no effect either partially or simultaneously on Return on investment, which are Profitability variables at Tencent Ltd. (influenced by a level of 6.93%). This condition indicates there is no increase in profitability from investment cash flows and dividend income.